Race, class and nationalism: the 1947 visit of Monty Naicker and Yusuf Dadoo to India, 1947 - Vahed, G.; Desai, A. (Faculty of the Humanities, University of the Free State, 2011)
This article focuses on a 1947 tour of India by two South African Indian doctors, Yusuf Dadoo and GM (Monty) Naicker, during which they met with Mohandas K Gandhi and Jawaharlal Nehru and attended the All-Asia Conference. The visit provides an opportunity to examine the links between Indians in the diaspora and homeland, and the issues that South Africans were grappling with – race, class, and nationalism, in the struggle against segregation and apartheid. In the decade that followed their visit, Dadoo and Naicker became national political figures and helped to break the racial boundaries around the anti-apartheid struggle. By the end of the 1950s, when armed struggle came to be seen by many activists as the only option to overthrow the apartheid regime, the communist Dadoo and Gandhian Naicker would part ways. While Naicker remained in South Africa, where he was subject to a series of banning orders, Dadoo went into exile to stitch together a broad coalition of forces. Into the twenty-first century Dadoo’s and Naicker’s ideological beacons are under intense pressure. Soviet Communism is dead, Gandhi’s India is proud of her nuclear arsenal, and the two doctors’ belief in non-racialism is under strain in their own country.
Keywords: Dadoo, Yusuf Mohamed; Naicker, Gangathura Mohambry; Anti-apartheid struggle